2004
DOI: 10.1116/1.1697483
|View full text |Cite
|
Sign up to set email alerts
|

Properties of c-C4F8 inductively coupled plasmas. II. Plasma chemistry and reaction mechanism for modeling of Ar/c-C4F8/O2 discharges

Abstract: Gas mixtures containing Ar, cC 4 F 8 , O 2 , and CO are often used for the plasma etching of silicon dioxide. Gas phase reaction mechanisms are required for first principles modeling of these systems to both provide insights to the plasma chemistry and to help optimize the process. In this article, results from computational and experimental investigations of the plasma chemistry of inductively coupled plasmas ͑ICPs͒ sustained in Ar, O 2 , Ar/c-C 4 F 8 and O 2 /c-C 4 F 8 gas mixtures with and without magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 91 publications
4
95
1
1
Order By: Relevance
“…The C 2 F 4 was generated from C 4 F 8 by electron impact. [33][34][35] The C 3 F 6 was mainly created by the removal of CF 2 species from C 4 F 8 . 8,[33][34][35] From these results, we found that the dissociation creating CF 2 species relatively increased at 2.0 Pa, then the CF 2 flux decreased when the pressure increased to 8.0 Pa owing to the low dissociation of C 4 F 8 .…”
Section: Measurement Of C 4 F 8 Dissociation In Pulsed Plasmamentioning
confidence: 99%
“…The C 2 F 4 was generated from C 4 F 8 by electron impact. [33][34][35] The C 3 F 6 was mainly created by the removal of CF 2 species from C 4 F 8 . 8,[33][34][35] From these results, we found that the dissociation creating CF 2 species relatively increased at 2.0 Pa, then the CF 2 flux decreased when the pressure increased to 8.0 Pa owing to the low dissociation of C 4 F 8 .…”
Section: Measurement Of C 4 F 8 Dissociation In Pulsed Plasmamentioning
confidence: 99%
“…[19]. Vasenkov et al [20] explored chemistry mechanism of the inductively coupled plasma of c-C 4 F 8 /Ar and c-C 4 F 8 /O 2 computationally and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…For conventional discharges, electron-impact driven species generation favors those species with the lowest threshold and so not only will radical formation be high, it may be difficult to control relative radical densities. 35 However, alternative approaches to plasma generation, such as electron beam generated plasmas, could offer additional paths for maintaining precursor molecule chemistry, where in depth characterization of the dissociation and radical generation pathways have the potential to produce significantly different chemistry as compared to more standard discharge plasma sources used today. 36 If the dissociation pathways of the precursor molecule are understood well, reverse engineering of etch mechanisms based on deposition chemistry 37 seems feasible even under plasma conditions.…”
Section: -34mentioning
confidence: 99%